Bridging the gap: Why regional forecasts must become local decisions - Gamoyo, Majambo; Ghosh, Aniruddha; Ahmed, Jemal S (2026)
At the 31st Southern Africa Regional Climate Outlook Forum (SARCOF-31) in Lusaka, the message was clear: we must Close the Early Warning Gap Together. This isn't just a theme; it's a call to action to move beyond simply predicting the weather and start protecting livelihoods.